ANALISIS PERUBAHAN TINGKAT KONSUMSI RUMAH TANGGA DI KABUPATEN SUMBAWA SEBELUM DAN SELAMA PANDEMI COVID-19 - Karmeli, Elly; Sumbawati, Rizka Ananda (Jurnal Ekonomi & Bisnis, 2025)
Covid-19 pandemic was a global health problem, including in Indonesia. The increase in COVID-19 cases has proven to have a significant impact on the global economy, Indonesia is no exception. Pandemi Covid-19 mempengaruhi ketahanan pangan baik secara langsung seperti mengganggu sistem pangan, maupun secara tidak langsung seperti pendapatan rumah tangga, akses dalam memperolah pangan dan kesehatan. Therefore, this study aims to analyze changes in household consumption levels in Sumbawa District before and during the Covid-19 pandemic. The type of this study was comparative study. The type of data used was quantitative data obtained directly from primary sources, namely the community in Sumbawa District, totaling 30 people. Respondents were determined by chance, so anyone who happened to meet the researcher and was willing to provide the information the researcher needed was used as a data source. Data collection in this study used structured interview techniques with interview guidelines. Data analysis in this study used the two-average difference test technique. The results of this study showed that there are a positive and significant difference in household consumption levels in Sumbawa District before and during the Covid-19 pandemic. Household consumption levels in Sumbawa District increased during the Covid-19 pandemic compared to before the Covid-19 pandemic. This increase was caused by higher food prices than before.